Monogenic Inflammatory Bowel Disease: It's Never Too Late to Make a Diagnosis - Vardi, Iddo; Chermesh, Irit; Werner, Lael; Barel, Ortal; Freund, Tal; McCourt, Collin; Fisher, Yael; Pinsker, Marina; Javasky, Elisheva; Weiss, Batia; Rechavi, Gideon; Hagin, David; et al. (Frontiers in Immunology, 2020)
Background: More than 50 different monogenic disorders have been identified as directly causing inflammatory bowel diseases, typically manifesting in the first years of life. We present the clinical course and immunological work-up of an adult patient who presented in adolescent years with an atypical gastrointestinal phenotype and was diagnosed more than two decades later with a monogenic disorder with important therapeutic implications. Methods: Whole exome sequencing was performed in a 37-years-old patient with a history of diarrhea since adolescence. Sanger sequencing was used to validate the suspected variant. Mass cytometry (CyTOF) and flow cytometry were conducted on peripheral blood mononuclear cells for deep immunophenotyping. Next-generation sequencing of the TCRB and IgH was performed for global immune repertoire analysis of circulating lymphocytes. Results: We identified a novel deleterious c.1455C>A (p.Y485X) mutation in LRBA. CyTOF studies demonstrated significant changes in immune landscape in the LRBA-deficient patient, including an increase in myeloid derived suppressor cells and double-negative T cells, decreased B cells, low ratio of naïve:memory T cells, and reduced capacity of T cells to secrete various cytokines following stimulation, including tumor necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ). In addition, this patient exhibited low frequency of regulatory T cells, with a reduction in their CTLA4 expression and interleukin (IL)-10 secretion. Finally, we show marked oligoclonal expansion of specific B- and T-cell clones in the peripheral blood of the LRBA-deficient patient. Conclusions: LRBA deficiency is characterized by marked immunological changes in innate and adaptive immune cells. This case highlights the importance of advanced genetic studies in patients with a unique phenotype, regardless of their age at presentation.